Railway system in New Zealand: Case study in strategic change - Cavana, R.Y (School of Management Working Papers, 1992)
The New Zealand railway system has undergone considerable changes over the past decade. Prior to 1 April 1982, the railway system was managed and controlled by the New Zealand Railways Department. This Department was frequently used as an instrument of the Government's social and economic policies, often in direct conflict with its commercial objectives. The New Zealand Railways Corporation was established on 1 April 1982, with a Board of Directors appointed with a wide range of business sector experiences. The major purpose of this restructuring was to allow the Corporation to run its operations on a more commercial basis. Regulations controlling competition from road transport of freight had been in place since the 1930's. These regulations were progressively released and finally removed in 1983 with the total deregulation of the road transport industry in New Zealand. The NZ Railways Corporation responded well to the restructured organisational environment and deregulated freight market by making dramatic gains in overall efficiency. However the financial costs of this restructuring were considerable, and by_ 1989, five years of increased net losses had reduced shareholders equity to 4% of total assets. The Corporation was on the verge of technical bankruptcy. This resulted in substantial restructuring of the NZ Railways Corporation balance sheet in 1990 and the establishment of New Zealand Rail Ltd on 28 October 1990. By June 1992, New Zealand Rail Ltd had been restored to profitability, showing a net profit of $36 million, equivalent to a return of 12% on shareholders funds. Staff numbers had been dramatically reduced to 5400, down from 21,600 in 1982. This paper examines the performance of the railway system in New Zealand from 1982 to 1992, during the period of considerable changes in the regulatory and institutional environment in which it operated. It also discusses the issue of future public or private ownership of the railway system in New Zealand.